Session 1 of the GASL Africa 1 regional virtual meeting, 2 September 2020 - International Livestock Research Institute (International Livestock Research Institute, 2020)
The Global Agenda for Sustainable Livestock (GASL) Africa 1 Regional online multi-stakeholder partners' meeting is one of eight organized by GASL and its anglo-phone Africa partners. The COVID-19 pandemic is a global issue with crucial short and long-term consequences. The Africa 1 regional (anglophone Africa) meeting sought to identify COVID-19 impacts and strategies from stakeholders responses that would contribute to building forward a more sustainable future from the livestock sector.